(NdEKORATIWNYE KOLLEKCIONNYE MINERALY (B/s - (NkIEWLENKO(B, (NeWGENIJ qKOWLEWI^s; (N~UPROW(B, (NwLADISLAW iWANOWI^s; (NdRAM[EWA(B, (NeLENA eWGENXEWNAs ((NmOSKWA (B:s (NnEDRA(B,s, 1987)
(NbIBLIOGR(B.: (NS(B. 220-221 (38 (NNAZW(B.)s
Keywords: (NmINERALOGIQs